Adolescents’ awareness of environmental care: experiences when writing short descriptive texts in english (2011)
Today it is necessary to approach environmental topics with students in an interdisciplinary manner to mitigate the environmental damages that the Earth is suffering. In this paper we report an actionresearch and innovation study aimed at sensitizing students with respect to the care and preservation of the environment through the writing of short descriptive texts in English. The study had four stages: motivation, knowledge of ecological vocabulary, production of sentences and paragraphs, construction of short descriptive texts with the help of guidance questions and their publication in the school newspaper. The findings show that the procedure used in class promotes interdisciplinary work around environmental topics as well as the development of writing skills.Hoy en día, es necesario abordar temas ambientales con los estudiantes, de manera interdisciplinaria, para mitigar los daños ambientales que está sufriendo la tierra. En este artículo reportamos un estudio de investigación-acción e innovación que buscó sensibilizar a los estudiantes acerca del cuidado y la preservación del medio ambiente mediante la escritura de breves textos descriptivos en inglés. El estudio tuvo cinco etapas: motivación; conocimiento de vocabulario ecológico; producción de frases y párrafos; construcción de breves textos descriptivos –con la ayuda de preguntas orientadoras–, y la publicación de los textos en el periódico escolar. Los resultados muestran que el proceso empleado en clase promueve el trabajo interdisciplinario en torno a temas ecológicos, así como el desarrollo de habilidades escriturales.